Development of new antigens for serologic diagnosis of animal trypanosomosis and their use for epizootic monitoring - Ch. Georgiou (Российский паразитологический журнал, 2021)
The purpose of the research is developing a method for obtaining erythrocyte antigens containing and not containing Trypanosoma equiperdum and T. evansi DNA, which can later be used in serological reactions to differentiate these types of Trypanosoma.Materials and methods. The studies were conducted in the Protozoology Laboratory and the Vyshnevolotsk Branch of the Federal State Budget Scientific Institution “Federal Scientific Centre VIEV RAS”, as well as livestock farms of the Russian Federation and other countries using clinical, microscopic, hematological, parasitological, biomolecular and serological methods.Results and discussion. Studies carried out for the first time have shown that it is possible to use erythrocyte antigens containing the T. equiperdum and T. evansi DNA obtained after 3-fold administration to mice and rabbits of a mixture of trypanosomal antigen with addition of 1.0 ml of an adjuvant (aluminum hydroxide), and bleeding of animals at 25 to 30 days. The formed precipitate was used as an antigen for serological tests. Experiments have shown that blood for preparation of positive serum can be taken when antibodies are in titers of 1:20 in the Prolonged Complement Fixation Test, and at least 1:400 in the Indirect Hemagglutination Test and ELISA, and for negative serum when horse blood serum reacts negatively with antigens of T. equiperdum and T. evansi in the Prolonged Complement Fixation Test, Indirect Hemagglutination Test and ELISA. The test systems of the Prolonged Complement Fixation Test, Indirect Hemagglutination Test and ELISA prepared by us with antigens containing and not containing T. equiperdum and T. evansi DNA resulted in creating a universal test system (Indirect Hemagglutination Test) for differentiating T. equiperdum from T. evansi.